Comparative efficacy of exogenous eCG and progesterone on endogenous progesterone and pregnancy in Holstein cows submitted to timed artificial insemination - Sampaio, Palmer de Castro; Alves, Nadja Gomes; Souza, José Camisão de; Sales, José Nélio de Sousa; Carvalho, R. J.; Lima, Renato Ribeiro; Teixeira, A. A.; Nogueira, Guilherme de Paula [UNESP]; Ascari, Ivan Júnior (Elsevier B. V., 2015)
The objectives were to evaluate the effects of the administration of either eCG or progesterone (P4) alone or combined on endogenous P4 concentrations and pregnancy per AI in lactating dairy cows. Cows received a P4-releasing intravaginal device (PRID) and estradiol benzoate on D-8. The PRID was removed and a PGF2α injection was given on D-3. An estradiol cypionate was given on D-2 and TAI was performed on D0. On D-2, cows were randomly allocated to treatments in a 2×2 factorial design: Control-saline solution on the D-2 and D+3 (n=104), eCG - 400IU eCG on D-2 (n=93), P4 - 600mg of P4 on D+3 (n=106), and eCG+P4 - 400IU eCG on D-2 and 600mg of P4 on D+3 (n=95). Blood samples were collected on days three, four, and thirteen and pregnancy diagnoses were performed at 32 and 46 days after AI. There was no interaction between eCG and P4 injection. Cows treated with eCG and with P4 injection had higher serum P4 on Day +4. On Day +13 serum P4 was lower in eCG-untreated primiparous cows (Interaction eCG×parity). Cows with serum P4<4.57ng/mL on Day +13 had lower probability to be pregnant on day 32. P/AI on days 32 and 46 and embryonic losses were not influenced by eCG and P4 injection. In conclusion, the addition of 400IU of eCG on D-2 and/or 600mg of P4 on D+3 to the present TAI protocol did not increase P/AI.
Keywords: Conception rate; Dairy cows; Equine chorionic gonadotropin; Late embryonic loss; Progesterone supplementation; Serum progesterone